Overnight Hospital Stay After Colon Surgery for Adenocarcinoma - Rogers, James P. (Society of Laparoendoscopic Surgeons, 2012)
A short hospital stay is one of the main advantages of the laparoscopic surgical technique. The process of developing and studying the “fast-track” process has contributed to a better understanding of the elements of perioperative care and has resulted in the reduction in length of stay (LOS) after colectomies. As we follow and refine this well-recognized multimodal approach, further decreases in the LOS can be expected. We present 2 octogenarian patients who, after receiving laparoscopic hemicolectomies for malignant disease, were discharged home <24 hours after their operations. Postoperative follow-ups did not show any adverse reaction to the early discharge. Modifying the multimodal perioperative technique with further refinement to the surgical technique appears to allow patients to be discharged home in the first 24 hours following laparoscopic colectomy.